Da’wah Study at The Islamic Social Construction of The Mafia Sholawat Congregation In Metro City - kurniawan, Siroy; Muhajir, Muhajir; Muzakky, Rois (Jurnal Ilmiah Syi'ar, 2023)
As a country with a majority Muslim population, Indonesia is here to give birth to a rich cultural treasure wrapped in Islamic nuances such as sholawat. Reading prayers within a religious framework is a form of praying for the Prophet Muhammad. The community of Sholawat Lovers, called the Sholawat Mafia, has diverse backgrounds, ranging from low levels of education, free association, and a lack of understanding of religion. In fact, it is not uncommon for this community to have arrogant attitudes such as fighting, dancing excessively during prayers, and even wearing inappropriate clothing. From this existing phenomenon, the author is interested in finding out the spirituality of the sholawat mafia congregation and analyzing it using Social Construction theory, with three stages, namely externalization, objectification and internalization. At each stage the author examines using 3 basic areas of Islam, namely Aqidah, sharia and morals. The externalization stage refers to the adaptation of the sholawat mafia community towards their intention to attend prayer activities, to obtain the blessings of Allah's grace and the Prophet's intercession. The objectification stage refers to understanding the existence of Allah, Allah's books, Prophets and Allah's angels. Apart from that, the objectification of the three basic principles of Islam is also formed by an attitude of solidarity between congregations which becomes a process of friendship. Meanwhile, the internalization stage is the result of the social form of the two stages. At this stage, the Sholawat mafia congregation feels peace of mind when praying. The Sholawat mafia does not discriminate between fellow humans. They consider that humans are in the wrong place and sin, so they should continue to be aware and compete in goodness.